Analysis of Social Capital in Community Forest Management (HKm) in Muaro Jambi Regency - Fajar Alan Syahrier; M. Wira Anshori; Galank Pratama; Mirza Sazeta; Azira Novia Rizal (LPPM Institut Pendidikan Nusantara Global, 2026)
This study analyses the form and role of social capital in the management of Community Forests(HKm) in Muaro Jambi District. Using a comparative qualitative approach, the study comparestwo HKm organisations with different institutional categories, namely the Koperasi Multi UsahaMandiri (gold category) and KTH Bumi Indah Sejahtera (blue category). Data collection wasconducted through in-depth interviews, observations, and documentation studies. The resultsshow that social capital in both groups is reflected in three dimensions: bonding, bridging, andlinking. The bonding dimension is strong in both groups, characterised by trust, mutualcooperation, and member participation. The bridging dimension developed better in KoperasiMulti Usaha Mandiri through horizontal networking with other cooperatives. The most decisivefactor was the linking dimension, which showed the most notable difference. The Multi-BusinessCooperative had strong vertical relationships with the village government and the forestryservice, thereby supporting institutional strengthening and improving the group's economicachievements. Conversely, KTH Bumi Indah Sejahtera has weak linking capital due to a lack ofcoordination with the village government, which has resulted in limited programme support andeconomic outcomes. This study concludes that the success of HKm management depends not onlyon internal cohesion, but primarily on the group's ability to build vertical networks to gain accessto resources and policy support.